(3eHGOF GdGbJUGOs - (3YGQa(B, (3Mehs; (3Ydj CHh TQGQ(B, s ((3YeGf(B:s (3OGQ GHf QTO ddfTQ(B,s)
(3eONd YGe ddEbJUGO, YfGUQ GdEfJGL, GdWdH hGdYQV, JMOjO GdCKeGf, GdESJgdGc hGdESJKeGQ, GdEfaGb GdMchej, GdONd Gdbhej hGdfGJL Gdbhej, GdCLhQ hGdHWGdI hGdJVNe, GdSjGSGJ GdfbOjI hGdeGdjIs
(3HHdhZQGajG U(B.140s
Keywords: (3GdEfJGLs; (3GdGbJUGOs; (3GdGbJUGO cdjs